CAREGIVER PARTICIPATION IN CHRONIC DISEASE SELF-MANAGEMENT EDUCATION PROGRAMS: FINDINGS FROM A NATIONAL STUDY. (11th November 2018) - Smith, M; Washington, T; Mingo, C; Towne, S; Cameron, K; Herrera-Venson, A; Ory, M; Kulinski, K
Abstract: Demand for formal and informal caregivers is expected to increase alongside rising chronic disease among the aging American population. Using data from a national dissemination of Chronic Disease Self-Management Education (CDSME) programs, this study examined the influence of self-reported caregiving status on successful program completion (i.e., attending 4+ of 6 offered sessions). Data were analyzed from 73, 317 middle-aged and older adults collected during CDSME workshops spanning 36 states and two territories. Data were collected from 2013–2016 by grantees and transferred to a national data repository. Logistic regression was used to identify characteristics associated with participant attendance in CDSME workshops. An interaction effect for caregiving status and the proportion of caregivers in the workshop was included in the same model as a sensitivity analysis. Overall, 74% of CDSME participants successfully completed workshops (77% for caregivers). Twenty-eight percent self-reported providing care to another person. On average, participants reported 2.6 chronic conditions. Participants who were caregivers (OR=1.13, P<0.001), female (OR=1.14, P<0.001), African American (OR=1.27, P<0.001), resided in rural areas (OR=1.27, P<0.001), and lived with others (OR=1.09, P<0.001) were more likely to successfully complete the intervention. Those who participated in workshops with more caregiver participants were more likely to complete the intervention (OR=1.45, P<0.001). However, the interaction effect between caregiving status and the number of caregivers in the workshop was associated with non-successful completion (OR=0.65, P<0.001). While caregivers were more likely to complete CDSME workshops, further research is needed to understand the critical mass of caregivers within a workshop to maintain sufficient attendance rates.